Fluorescent Markers for Amyloid‐β Detection: Computational Insights. Issue 7 (1st December 2016) - Peccati, Francesca; Pantaleone, Stefano; Solans‐Monfort, Xavier; Sodupe, Mariona
Abstract: In vivo detection of cerebral amyloid‐β plaques is essential for an early diagnosis of Alzheimer′s disease. Optical imaging, which employs fluorescent markers emitting in the near‐infrared range, is a growing alternative to nuclear techniques, with indisputable advantages. The rational design of amyloid markers requires optimization of both the optical and binding properties, and of their mutual interaction. In this work, the structural aspects that determine the performance of selected amyloid markers have been analyzed, focusing on the contributions offered by computational techniques. Abstract :